Leader–Member Exchange, Work Engagement, and Psychological Withdrawal Behavior: The Mediating Role of Psychological Empowerment - Aggarwal, Arun; Chand, Pawan Kumar; Jhamb, Deepika; Mittal, Amit (Frontiers in Psychology, 2020)
Perceptions of psychological empowerment play a vital role in the way an individual perceives things at the workplace. In spite of this, there is scant research on the antecedents and consequences of psychological empowerment. This study is an attempt to fill this gap by analyzing the mediating role of psychological empowerment on the relationship between its antecedents (leader-member exchange) and its consequences (work engagement and psychological withdrawal behavior). Data was collected from 454 employees working in the Research and Development (R&D) department of information technology and pharmaceutical sector operating in India. Results suggest that employees who have a high-quality relationship with their leader have high psychological empowerment, they are highly engaged at work and their psychological withdrawal behavior is also low. In addition to this, high levels of psychological empowerment have a positive impact on their engagement towards work with further leads to low psychological withdrawal behavior. The theoretical and practical implications of these results are discussed.